The Green Solution to Water Shortage in Rural Area - Mohd Nazaruddin Yusoff, Azlizan Talib, Amirulikhsan Zolkafli, Muhamad Azwan Abd Rahman, Mohd Fitri Abdul Rahman, Sharif Shofirun Sharif Ali (International Journal of Advanced Science and Technology, 2020)
Malaysia is one of the countries which received a large amount of rainfall which ideal for rainwater harvesting. As rainwater harvesting is a sustainable solution, it enables the reduction of the risk of water rationing and flooding. The technology behind the rainwater harvesting is effortless which can be easily adopted on any new or existing building. Therefore, the purpose of this article is to argue the sustainability and effectiveness of rainwater harvesting for the residential area at Kampung Bukit Lada and Kampung KEDA Bendang Perang. This project was executed using theoretical and practical short-term training methods to develop skills and innovation among rural youth in producing a sustainable product. The project also potentially as a solution for water shortage issue in the area which is experiencing low water pressure problems. The study concludes that the adoption of rainwater harvesting technology has certainly made residential societies self-sustainable.